2017
DOI: 10.1007/jhep06(2017)012
|View full text |Cite
|
Sign up to set email alerts
|

RG stability of integrable fishnet models

Abstract: Abstract:We address the question of perturbative consistency in the scalar fishnet models presented by Caetano, Gürdogan and Kazakov [1,2]. We argue that their 3-dimensional φ 6 fishnet model becomes perturbatively stable under renormalization in the large N limit, in contrast to what happens in their 4-dimensional φ 4 fishnet model, in which double trace terms are known to be generated by the RG flow. We point out that there is a direct way to modify this second theory that protects it from such corrections. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 39 publications
1
36
0
Order By: Relevance
“…On the other hand, the example that we are discussing here is stronger, because we do have exactly marginal operators in the conformal theory. Other examples of conformal manifolds in non-supersymmetric theories were recently found by relaxing the constraint of unitarity [75,76]. marginality constraints.…”
Section: Goldstone Bosons and Conformal Manifoldmentioning
confidence: 99%
“…On the other hand, the example that we are discussing here is stronger, because we do have exactly marginal operators in the conformal theory. Other examples of conformal manifolds in non-supersymmetric theories were recently found by relaxing the constraint of unitarity [75,76]. marginality constraints.…”
Section: Goldstone Bosons and Conformal Manifoldmentioning
confidence: 99%
“…The planar limit corresponds to sending N → ∞ at fixed g 2 and the theory is conformal for any g 2 . In particular, no double-trace interactions are needed here [72]. The simplest single-trace operator is the BMN vacuum operator…”
Section: D Fishnet Graphsmentioning
confidence: 99%
“…These models, although not being unitary, are interesting in many respect, but they also share the presence of double-trace operators in the effective action which spoil conformal invariance at leading order in 1/N . In a more recent work [40], it was suggested that a suitable refinement of these models (that is, introducing an extra flavor structure for the component fields) could project out the double-trace operators, at least at leading order in 1/N , similarly to [37]. And that also three and six-dimensional versions of the same model are not plagued by double-trace operator running, at large N .…”
Section: Jhep11(2017)167mentioning
confidence: 99%